Recurrent neural networks for generalization towards the vessel geometry in autonomous endovascular guidewire navigation in the aortic arch - Karstensen, Lennart; Ritter, Jacqueline; Hatzl, Johannes; Ernst, Floris; Langejürgen, Jens; Uhl, Christian; Mathis-Ullrich, Franziska (International journal of computer assisted radiology and surgery, 2023)
Endovascular intervention is the state-of-the-art treatment for common cardiovascular diseases, such as heart attack and stroke. Automation of the procedure may improve the working conditions of physicians and provide high-quality care to patients in remote areas, posing a major impact on overall treatment quality. However, this requires the adaption to individual patient anatomies, which currently poses an unsolved challenge.